Racism, xenophobia, antisemitism, and Islamophobia in European football: symptoms, sources, and solutions - Merkel, Udo (Critical research in football, 2025)
This book examines the prevalence of racism, xenophobia, antisemitism, and Islamophobia in European football. It provides critical assessments of selected policies, strategies, campaigns, and initiatives that have been developed by various stakeholders aimed at combating these discriminatory practices.